Electrospun aeolotropic electrically conductive neoteric janus nanostrips array functionalized by enhancive up-conversion luminescence and magnetism. (September 2020) - Yang, Xiuling; Tian, Jiao; Qi, Haina; Sheng, Yuqi; Xie, Yunrui; Yu, Wensheng; Dong, Xiangting
Graphical abstract: Highlights: Coaxial nanobelt//nanobelt typed Janus nanostrip is firstly designed and constructed. Partition of three independent areas in Janus nanostrip is microscopically realized. Partitioned structure helps reduce detrimental interactions among various materials. Janus nanostrips array has tuned aeolotropy, magnetism and upconversion luminescence. Neoteric techniques are established to construct exceptive Janus nanostrip and array. Abstract: Study on luminescent-electrically conductive-magnetic multifunctional nanomaterials has become one of the hotspots in the field of new materials owing to their unique properties and wide potential applications. In this work, [CoFe2 O4 /polymethylmethacrylate (PMMA)]@[polyaniline (PANI)/PMMA] coaxial nanobelt//[Y2 O3 :Yb 3+, Er 3+ /PMMA] nanobelt structured Janus nanostrip and Janus nanostrips array (termed as [M@E]//UL JNA) are designed and prepared by peculiarly devised and manufactured electrospinning equipment. The distinct Janus nanostrip is composed of electrically conductive-magnetic difunctional [CoFe2 O4 /PMMA]@[PANI/PMMA] coaxial nanobelt and insulative up-conversion luminescence (UL) [Y2 O3 :Yb 3+, Er 3+ /PMMA] nanobelt. Partition of three freestanding areas in Janus nanostrip is microscopically realized, and thus three functional substances are effectually limited to their own area to avert adverse mutual impact among different functions of aeolotropic conduction, magnetism and up-conversion luminescence. Neoteric Janus nanostrip is employed as building unit to ensure and endue the [M@E]//UL JNA with concurrent excellent polyfunctionality of aeolotropic conduction, magnetism and up-conversion luminescence. Formation mechanisms of peculiar-typed Janus nanostrip and their array are advanced, and novel techniques are established to construct exceptive Janus nanostrip and array. The flexible and processable [M@E]//UL JNA has potential applications in optical devices and conductive materials owing to the peculiar structure and performances. The neoteric technique provides a pathway to prepare other polyfunctional nanomaterials.